Genetic characterization of 32 X-InDels in a population sample from São Paulo State (Brazil) - Martinez, Juliana [UNESP]; Polverari, Fernanda Silva [UNESP]; Silva, Flávia Alves de Jesus [UNESP]; Braganholi, Danilo Faustino [UNESP]; Ferraz, Joyce Aparecida Martins Lopes; Gusmão, Leonor; Cicarelli, Regina Maria Barretto [UNESP] (Springer Nature, 2019)
X-chromosomal markers can be useful in some forensic cases, where the analysis of the autosomal markers is not conclusive. In this study, a population sample of 500 unrelated individuals born in São Paulo State was characterized for 32 X-InDel markers. No deviations from the Hardy–Weinberg equilibrium were detected, except for MID1361. The 32 X-InDels showed an accumulated power of discrimination of 0.9999999999993 in females and 0.99999993 in males and an exclusion chance of 0.999996 in trios and 0.99995 in duos. São Paulo showed lower genetic distances to the Colombian admixed and European populations than to Native American, Asian, or African populations. Ancestry analysis revealed 41.8% European, 31.6% African, and 26.6% Native American contributions. Segregation analysis was performed in 101 trios, and the mutation rate was estimated to be low.
Keywords: Forensic genetics; Human identification; Insertion/deletion polymorphism; Kinship testing; X chromosome